Managing the distributional effects of energy taxes and subsidy removal in Latin America and the Caribbean - Kuishuang Feng; Klaus Hubacek; Yu Liu; Estefanía Marchán; Adrien Vogt-Schilb (Inter-American Development Bank (IDB), 2018)
Energy subsidies have been criticized due to their economic inefficiency and promotion of wasteful usage of energy and associated carbon emissions. Conversely, environmental taxes are advocated as efficient policy instruments. Nonetheless, removing subsidies and taxing energy can be politically challenging because vulnerable households rely on low energy prices. This study analyzes the impact of energy price increases on different income quintiles groups in eleven Latin American and Caribbean countries using an energy-extended input-output approach. Our results show that higher-income groups benefit more from low energy prices than low-income groups when tracing both the direct and indirect (supply chain) effects of energy price variations. Energy subsidies are a very expensive option to transfer income to poor households. Across the countries considered, using energy subsidies it would cost about 12 to transfer 1 of income to households in the poorest quintile. Recycling a small fraction of fiscal revenues from energy subsidy removal or energy taxation could be sufficient to compensate vulnerable households from the effects of price hikes. Our findings suggest that cash transfers to poor households and targeted subsidies for public transportation or food are the most effective measures to compensate households for welfare loss.
Keywords: H22; H23; Q01; N56; O13; 330; distributional impact; energy taxes; subsidy removal; input-output analysis; carbon taxes; environmental tax reform; political acceptability